Caracterização de ametistas naturais - Eduardo Henrique Martins Nunes (2008)
This research intends to investigate the formation of color in samples of natural amethyst from different origins after submitting them to gamma irradiation, as well to develop an identification method of uncolored crystals with potential for development of color. The techniques of infrared spectroscopy, ultraviolet-visible spectroscopy and atomic emission spectroscopy combined with neutron activation analysis, electronicparamagnetic resonance and thermoluminescence experiments will be used to characterize and to study the impurities and defects in samples of natural amethyst. We observe that samples with high iron concentration, exhibit low aluminum concentration and vice-versa. This is an indication that there is a competition between iron and aluminum atoms to occupy the silicon site in the quartz structure during thecrystal formation. The amethyst samples have generally high iron contents. This evidences the role of the iron in the color formation of this mineral. In the prasiolite samples we observed a high aluminum concentration. This suggests that a large fraction of the iron atoms in the prasiolite is at interstitial sites, because the probability that thesilicon site is occupied by an aluminum atom is high. Using intrinsic characteristics of the infrared spectrum of each material used in thisstudy, we developed three identification methods of colorless crystals with potential to develop color. These methods are very important because they allow accomplishing the test at anyplace where there is an available spectrometer. The + + + + 3i043Si Fe ] /M O [Fe complex, present at colorless amethyst structure, is responsible for the bands at 220 nm and 265 nm. During the irradiation, these defects transform in the amethyst color centers, constituted by the + + + 2i o 4 4Si Fe ] O [Fe complex. This complex generates absorption bands at 370 nm and 545 nm. During the annealing that transforms amethyst in citrine, occurs the precipitation of Fe2O3 particulates. We believe that the iron atoms which compose the Fe2O3 particulates come from Fe3+ ions at interstitial sites because the +3 Si Fe precipitation is unlikely due to the high covalent character of the O Fe bond. In this work, differently of the proposed by others scientists, it was not attributed a direct role to the ironparticulates in the citrine color. We propose that in citrine there are no amethyst color centers and that this mineral color is due to the prolongation of the ultraviolet absorption bands into the visible region of the electromagnetic spectrum. The absorption band at 210 nm, present in the prasiolite spectrum, suffers considerable intensity increase after the material irradiation due to the 0 22] ) ( [ OH Fei+ centers formation. Amethyst color centers have discreet presence at prasiolita, explaining why the bands at 370 nm and 545 nm have low intensities. Another factor to be considered is the high presence of impurity atoms in the prasiolite structure. This is an indication that there are large distortions at the structure of this material, since the presence of impurity atoms generates tensions in the quartz structure. Such distortions may cause thedisplacement of the absorption bands present in the amethyst spectrum to larger wavelengths in prasiolite. Furthermore, these distortions may be responsible fonoises observed in the prasiolite infrared spectrum